EFFECT OF POTENTIAL RESOURCES OF OCCUPATIONAL HAZARDS AND RISKS ON THE JLS LOT 6 PROJECT TULUNGAGUNG TRENGGALEK USING JSA METHODS AND HIRARC METHODS - Fatimah, Siti (Universitas Negeri Malang, 2021)
Abstract: Work hazards and risks in construction work are things that must be considered because construction work is a job that has a higher work risk compared to other jobs. One of the impacts of occupational hazards and risks that often occurs is work accidents, according to BPJS Employment data in the construction sector in 2020 there were 153,044 work accidents. One of the actions to overcome high work accidents is by identifying and assessing the source of the hazard using the Job Safety Analysis (JSA) method and the work risk using the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method. This study aims to identify and take into account the level of hazards and occupational risks and their control in structural work, excavation work, and road pavement work in the JLS Lot 6 project with a quantitative and correlative descriptive research design. The first stage is by conducting a literature study followed by observation and distributing questionnaires. Processing of data from the questionnaire results to determine the rate of assessment of the source of hazards and occupational risks adjusted to the scale of each method used. The results of the study using the JSA method from 39 identified hazard sources, there were 30 in category 1 (acceptable), 8 in category 2 (priority 3), and 1 in category 3 (substantial). The results of the assessment of hazard sources with the highest value of 71.49 related to the transportation of excavated products in earthworks excavation work, and the lowest value of 4.3 on asphalting work, namely smoke and heat on asphalt combustion. The results of the study using the HIRARC method obtained 45 occupational risks with 34 in the low category (low) and 11 in the medium category (medium). The work risk assessment with the highest score of 3.98 was related to the spread of Covid-19 which caused work delays, as well as injuries to the legs and head due to not using PPE, while the lowest score was 1.82 related to falling, slipping, and being hit by heavy equipment on the job. box culvert. The results of the control carried out are improving the technical aspects of heavy equipment, and tightening and maintaining the protocol for using PPE during the Covid-19 period correctly. The results of simple linear regression with hypothesis testing f and t stated that the source of the hazard had a partial and simultaneous effect on work risk with a degradation value of 44.9%.Keywords: Hazard Source, Occupational Risk, JSA, HIRARC, JLS Project Lot 6